2010
DOI: 10.1002/bltj.20401
|View full text |Cite
|
Sign up to set email alerts
|

40 Gb/s DBPSK and DQPSK formats for transparent 50 GHz DWDM transmission

Abstract: Today's dense wavelength division multiplexed (DWDM) (ILs), and arrayed waveguide grating (AWG) multiplexers and demultiplexers, support channel routing in several different directions, yielding so-called multidegree mesh ROADM. Transparently transporting high capacity DWDM channels through such an optical network is a challenge due to several physical impairments that are associated with the approach, and investigations are being continuously pursued to enhance the overall system performance.In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
3
Order By: Relevance
“…In contrast to typical laboratory studies where a single device is placed in a short recirculating loop to emulate filter concatenation [3], we included up to six different, non pre-selected interleavers for these concatenation experiments. Hence, our measurements also capture typical variations in center frequency, bandwidth, and filter dispersion.…”
Section: Dwdm and Roadmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to typical laboratory studies where a single device is placed in a short recirculating loop to emulate filter concatenation [3], we included up to six different, non pre-selected interleavers for these concatenation experiments. Hence, our measurements also capture typical variations in center frequency, bandwidth, and filter dispersion.…”
Section: Dwdm and Roadmsmentioning
confidence: 99%
“…The 50/100 GHz interleavers have the narrowest bandwidth and thus are the limiting filters in the system. Many studies have been reported that examine the effects of filter concatenation on high-speed optical signals (see, e.g., [3] and [30]). Thus it is important to understand these limitations when specifying an upgrade to higher speed signals that may have larger optical bandwidths.…”
Section: Dwdm and Roadmsmentioning
confidence: 99%
“…Em 10 Gb/s, os sistemas de transmissão óptica são baseados em modulação de intensidade (OOK), porém com o avanço das taxas de transmissão, a ocupação espectral necessária para a manutenção da grade DWDM (50 GHz) forçou a evolução das estruturas de transmissão e recepção com o intuito de aumento da eficiência espectral. Neste contexto, os sistemas de 40 Gb/s passaram a operar, em sua maioria, com estruturas de transmissão com modulação de fase e codificação diferencial com dois bits por símbolo (DQPSK), enquanto que a estrutura de recepção passou a necessitar de um interferômetro para a realização da recepção de forma diferencial, extraindo a informação da diferença de fase entre bits sucessivos [3]. Nestes sistemas a eficiência espectral evoluiu de 0,5 b/s/Hz (sistemas OOK) para 1b/s/Hz, tornando possível a transmissão de sinais a 40 Gb/s na grade DWDM.…”
Section: Introductionunclassified
“…O terceiro bloco do sistema óptico, denominado de receptor (Figura 1.c), é composto por um pré-amplificador (EDFA) seguido de um filtro óptico sintonizável de largura 200 GHz, responsável pela filtragem do ruído óptico introduzido pelo sistema de amplificação e uma híbrida de 90º, responsável pela demodulação do sinal óptico DP-QPSK. Este componente realiza a conversão do campo magnético do sinal óptico para o domínio elétrico de forma linear [3], amostrado em seguida por conversores AD de alta-taxa e banda elétrica elevada, possibilitando aplicar técnicas de processamento digital e compensar os efeitos lineares e não-lineares sofridos pelo sinal ao longo de sua propagação.…”
Section: Introductionunclassified
“…Transmission structures with phase modulation and differential coding (DQPSK) and interferometerbased reception for phase difference extraction were used for 40-Gb/s systems [4]. These systems improved the spectral efficiency from 0.5-b/s/Hz (OOK) to 1-b/s/Hz (DQPSK).…”
mentioning
confidence: 99%